Réponses

Meilleure réponse !
2012-11-04T19:25:24+01:00

Bonjour,

 

Exo 2

 

A=3(3\sqrt{2})^2-2(3\sqrt{2})+1=3*9*2-6\sqrt{2}+1=55-6\sqrt{2}=

A=46,514

 

A=3(\frac{\sqrt{2}}{3})^2-2\frac{\sqrt{2}}{3}+1=\frac{3*2}{9}-2\frac{\sqrt{2}}{3}+1=

 

A=\frac{2}{3}-2\frac{\sqrt{2}}{3}+1=\frac{3+2-2\sqrt{2}}{3}}=\frac{5-2\sqrt{2}}{3}}=0,723

 

exo3-1

 

 a)

104,501²=(104501*10^-3)²=10451²*10^-6=10920,459001

 

b)

104501000²=(104501*10^3)²=104501²*10^6=10920459001*10^6

 

c)

\sqrt{10920459001}=104501

 

d)

 \sqrt{1092045,9001}=\sqrt{10920459001*10^-4}=104501*10^-2=1045,01

 

exo3-2

 

\sqrt{109204590010}=\sqrt{10920459001*10}=\sqrt{10}*\sqrt{10920459001}

 

Il faut donc multiplier par \sqrt{10}

 

J'espère que tu as compris

 

A+ 

 

 

2012-11-04T21:29:01+01:00

 

 

 A=2(3racine2)^2-2(3racine2)+1=3*932-6racine2+1=55-6racine2=46,5141863=46,514

 

a=3(racine2/3)^2-2(racine 2/3)+1=(3*2/9)-2(racine 2/3)+1=2/3-2(racine 2/3)+1

(3+2+2racine2)3=(5-2racine2)/3=0,723857625=0,723

 

 a)104,501²=(104501*10^-3)²=10451²*10^-6=10920,459001

 

b)104501000²=(104501*10^3)²=104501²*10^6=10920459001*10^6

 c)racine10920459001=104501 

d)racine1092045,9001 =racine10920459001*10puissance-4=104501 *10puissance-2=1045,01 

 

 racine 109204590010=racine 10920459001*10= racine de 10*racine 10920459001

il faut mutiplier par racine de 10

bonne chance